Spiritual Leadership Practices and Their Role in Promoting Proactive Behavior: An Analytical Study of The Opinions of a Sample of Teaching Staff in The Faculties of Salah al-Din University / Erbil - خالد محمد خال سارا; خالد مصطفى احمد (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
Objective: The current study aimed to analyze the relationship and impact of the spiritual leadership of the leaders of the faculties of Salah al-Din University, represented by its dimensions (vision, faith and hope, altruism, meaning) in the dimensions of proactive behavior represented by (voice behavior, responsibility, individual innovation, preventing problems). General framework: The general framework of the study represents a set of axes represented by the problem of the study, which identified by raising several questions about the nature of the relationship, the impact, and the variance between the independent variable (spiritual leadership) and the dependent variable (proactive behavior). To verify the validity of the hypotheses, all of them were subjected to multiple tests, and the study used a questionnaire as a means to obtain data. Study Methodology: The study followed the descriptive analytical approach, where the main and sub-variables were described, as well as to analyze the relationships and impact between the study variables. Study Population: The study population represented the colleges of Salah al-Din University in the city of Erbil, which numbered 15 colleges. Study sample: The study sample represents faculty members in the faculties of Salah al-Din University / Erbil, and the number of respondents was (405) members. Hypothesis testing: The hypotheses were tested by applying statistical methods using the computer program (SPSS V.22). Conclusions: The study reached a set of main conclusions, including the results of the correlation analysis revealed the existence of positive moral relationships at a high level between spiritual leadership and proactive behavior at the macro and micro levels, and this confirms the benefit of the researched colleges from the practices of spiritual leadership and its contribution to stimulating the proactive behavior of teaching staff. In addition, there is a positive and significant effect of the spiritual leadership variable on the proactive behavior variable, according to what was revealed by the analysis indicators at the overall level. The regression results also indicated the presence of an effect for each dimension of spiritual leadership (vision, faith and hope, altruism, meaning). Respectively, the dimensions of proactive behavior (vocal behavior, taking responsibility, individual innovation, preventing problems). Recommendation: Work to deepen the concept of spiritual leadership in the administration of the colleges investigated, as the study found a significant correlation between spiritual leadership and the proactive behavior of teaching staff, through: Subjecting college administrations at Salah al-Din University to training courses to introduce them to the concept of spiritual leadership, and how their application of spiritual leadership will It leads to: Strengthening the spiritual standards of the teaching staff by gaining their trust and loyalty to the university in question, increasing the teaching staff’s satisfaction with the work environment and deepening their spiritual connection with it, and stimulating their proactive behavior which leads to the renewal of scientific procedures and activities on an ongoing basis.